Safety and efficacy of laryngeal mask airway placement in term of oropharyngeal leak pressure: A comparison between conventional insertion and laryngoscope guided insertion - Ayan Ghorui; Baisakhi Laha; Sandip Roy Basunia; Debasish Saha (Asian Journal of Medical Sciences)
Background: The effectiveness of laryngeal mask airway (LMA) through conventional insertion technique versus laryngoscope-guided insertion is a debatable issue. Use of only fiberoptic scoring for assessment has shown conflicting results. A newly presented clinical sign – oropharyngeal leak oropharyngeal leak pressure (OLP) – is showing promise for assessing airway sealing in LMA placement.